Episiotomy-related perineal pain and breastfeeding self-efficacy among postpartum mothers - Bilgin, Zümrüt; Küçükoğlu, Seda (Pediomaternal Nursing Journal, 2024)
Introduction: Episiotomy-related perineal pain may significantly impact breastfeeding self-efficacy, influencing new mothers' ability to successfully initiate and maintain breastfeeding. The aim of this study was to determine the relationship between MPQ-SF and postpartum BSES-SF scores. Methods: This descriptive study was conducted at a maternity hospital in Istanbul and involved 208 volunteer mothers who had undergone an episiotomy during childbirth. Data were collected using a “Participant Information Form,” the “McGill Pain Questionnaire-Short Form,” the “Postpartum Breastfeeding Self-Efficacy Scale-Short Form,” and the “Visual Analogue Scale.” The data were analyzed using a statistical program, with significance set at P-value < 0.05. Results: The average age of the mothers was 27.29 ± 5.88 years, with 44.7% experiencing their first childbirth. Severe perineal pain was reported by 9.1% of the mothers, and 35.6% indicated that this pain affected their ability to breastfeed. A significant relationship was found between perineal pain and both the McGill Pain Questionnaire score and breastfeeding self-efficacy score (P-value < 0.05). Additionally, there was a negative correlation between postpartum McGill Pain Questionnaire scores and postpartum breastfeeding self-efficacy scores (P-value < 0.05). Conclusion: Postpartum perineal pain affected mothers' breastfeeding self-efficacy. It is recommended to take measures to reduce perineal pain that negatively affects mothers' breastfeeding. Keywords: breastfeeding; episiotomy; perineal pain; postpartum; self-sufficiency